Analysis of volatile components in Dalbergia cochinchinensis Pierre by a comprehensive two‐dimensional gas chromatography with mass spectrometry method using a solid‐state modulator. Issue 23 (12th November 2018) - Xiang, Zhangmin; Chen, Xiaotian; Zhao, Zhijun; Xiao, Xue; Guo, Pengran; Song, Huacan; Yang, Xi; Huang, Minghua
Abstract: Volatile components in Dalbergia cochinchinensis Pierre were analysed using a comprehensive two‐dimensional gas chromatography with mass spectrometry method featuring a new solid‐state modulator. Compared to one‐dimensional gas chromatography, the number of detected peaks were significantly increased. A total of 45 major compounds were identified in this study and the forward and reverse match factors of these compounds were both above 800. The results showed that the volatile components in Dalbergia cochinchinensis Pierre were primarily aldehyde and ketone compounds such as benzaldehyde, cinnamaldehyde, 4‐chromanone, 1‐(2‐hydroxyphenyl)ethanone and acetophenone. In addition, a semi‐quantitative analysis was conducted to determine the contents of the detected compounds based on peak area percentage. Moreover, the repeatability of the comprehensive two‐dimensional gas chromatography‐mass spectrometry analysis in this study was quite satisfactory with relative standard deviations less than 12.7% for intraday and 17.3% for interday measurements.